2013
DOI: 10.1002/jgrd.50719
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the surface radiation budget over the Tibetan Plateau with ground‐measured, reanalysis, and remote sensing data sets: 2. Spatiotemporal analysis

Abstract: [1] Recent progress in observation and modeling studies indicates that the Tibetan Plateau (TP) has been experiencing solar dimming coincident with changes of surface and atmospheric conditions since the early 1980s. However, changes and variability of the surface radiation budget over the entire Tibetan Plateau have rarely been analyzed in association with meteorological observations. Taking into consideration the limitations in ground measurements, reanalysis products, and remote sensing products, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Compared to the published studies, the LandFlux-EVAL LE also corresponds well with the merged net radiation and LE datasets, which were developed and validated over the TP by Shi and Liang (2013a, b) and Shi and Liang (2014). The spatial distribution of annual mean net radiation and LE can be found in study of Shi and Liang (2013a) and Shi and Liang (2014). Although the LandFlux-EVAL has not been validated against in situ measurements over the TP, the similar spatial patterns between LE and both observation-based precipitation and validated radiation to some extent demonstrate the validity of LandFlux-EVAL over the TP.…”
Section: Spatial and Temporal Variability Of Different Le Productssupporting
confidence: 53%
See 1 more Smart Citation
“…Compared to the published studies, the LandFlux-EVAL LE also corresponds well with the merged net radiation and LE datasets, which were developed and validated over the TP by Shi and Liang (2013a, b) and Shi and Liang (2014). The spatial distribution of annual mean net radiation and LE can be found in study of Shi and Liang (2013a) and Shi and Liang (2014). Although the LandFlux-EVAL has not been validated against in situ measurements over the TP, the similar spatial patterns between LE and both observation-based precipitation and validated radiation to some extent demonstrate the validity of LandFlux-EVAL over the TP.…”
Section: Spatial and Temporal Variability Of Different Le Productssupporting
confidence: 53%
“…The LandFlux-EVAL benchmark product was found to agree well with observation-based precipitation, in situ measurementsvalidated radiation (Shi and Liang, 2013a), and in situ measurements-validated LE product (Shi and Liang, 2014). From this point of view, it can be served as the reference dataset.…”
Section: Discussion On the Different Performance Of The Le Datasets Omentioning
confidence: 64%
“…There are multiple factors resulting in the variations at different spatial and temporal scales. He et al (2013) found from the GLASS albedo product that a large decrease in surface albedo over Greenland after 2000 ((0.0024 yr (1 ) mainly occurred at Shi and Liang (2013) found that the albedo increase over Tibetan Plateau is highly correlated with the increase in snow cover. More studies are necessary to evaluate the causes of the variations in albedo.…”
Section: Glass Albedo Productmentioning
confidence: 99%
“…According to Equation (6), the surface broadband albedo can be estimated from narrowband albedo [47], () n n c      (13) where is the band number of satellite sensors, is the narrow-to-broadband conversion coefficient of band .…”
Section: Discussionmentioning
confidence: 99%
“…The global land surface albedo changes with natural processes and human activities [6], such as deforestation [7,8], desertification [9], wildfire [10], and the decreasing of northern-hemisphere snow and sea-ice [11][12][13]. These changes in surface albedo also influence regional and global weather [14] in which even tiny variations of surface albedo can feedback to the climate system and affect the global and regional climate patterns.…”
Section: Introductionmentioning
confidence: 99%